SISTEM PENDUKUNG KEPUTUSAN PENILAIAN KINERJA JASA PRAMUBAKTI MENGGUNAKAN METODE MOORA - Hamria Hamria Hamria; Azwar Azwar; Khaerul Arja (Teknik Informatika, 2020)
Decision support system is a system that can help problems that can help problems that occur for decision making quickly and can know the highest to lowest value to determine the selection results. In this research there is a case study which is an example of solving a problem with a decision support system, where the problem of the case at the Boalemo District Police is how to conduct performance appraisal of pre serving services that still use the manual method making the performance appraisal process take a long time to get results. Therefore created a system that supports decisions that can help the assessment process. This study aims to test the performance and effectiveness of the decision support system of the Pramubakti service performance assessment using the MOORA method as a basis for decision making. Based on the results of research that has been carried out it can be concluded that the system can assist the decision makers in carrying out performance appraisals quickly. Evidenced by the results of testing conducted with the white box testing method and base path testing which produces a value of V(G) = 4 CC, so it is obtained that the logic of the flowchart calculation of normalization and assessment is correct based on black box testing which includes test input processes and output with reference to software design has been met with results in accordance with the design.